Analysis of the Quality Parameter Requirements of National Standard Development for Battery Swap in Electric Vehicles - Widia Citra Anggundari; Auraga Dewantoro; Bendjamin Benny Louhenapessy; Rika Dwi Susmiarni; Yopi Yopi; Nur Tjahyo Eka Darmayanti (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2021)
The electric vehicle industry is expected to increase from year to year. Electric vehicles used energy stored in battery packs. The battery requires a long energy charge when the energy in the battery runs out. The solution to this energy charging time is a battery swap system. The purpose of this study was to analyze the parameters of the quality requirements for the development of a national standard battery for electric vehicles. The sampling method was carried out by non-probability sampling with a purposive sampling method. Respondents consist of various types of stakeholders who are directly related to electric vehicles so that this approach is expected to be able to answer the needs of the standard parameters of electric vehicle swap batteries in Indonesia. Data were analyzed using descriptive analysis. Based on the research results obtained several parameters, namely the type of battery, battery size and dimensions, security system requirements, communication, protection against electric shock, equipment construction requirements, electromagnetic compatibility, and marking and instructions. It is expected that these parameters can be taken into consideration for inclusion in the Indonesian National Standard governing battery swap in electric vehicles.